Pengaruh Sertifikasi Dosen terhadap Kinerja Dosen Universitas Kristen Indonesia Toraja - Wenly Pata’ Langi’ (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2025)
The purpose of this study is to determine the effect of lecturer certification on the performance of lecturers at the Universitas Kristen Indonesia Toraja. This study uses a quantitative method with a multiple linear regression approach, and data processing was carried out using SPSS version 23. The data collection procedures included observation, interviews, questionnaires, and documentation. The study involved 56 respondents who were selected using simple random sampling with the Slovin formula. The results of the t-test showed that lecturer certification has a significant effect on lecturer performance. This was evidenced by the significance value of 0.000 (p < 0.05) and a t-value of 7.099, which is greater than the t-table value of 2.005. This means that lecturer certification (variable X) positively affects lecturer performance (variable Y). The conclusion of this study is that lecturer certification has a positive and significant impact on improving lecturer performance at Universitas Kristen Indonesia Toraja. This study recommends that the university pay attention to the importance of lecturer certification to support the improvement of teaching quality and lecturer performance in the future.